Characterization of Cr implanted GaAs processed with ArF and Nd-YAG laser melting - Algaidy, Sari; Caudevilla, Daniel; Benítez-Fernández, Rafael; Duarte-Cano, Sebastián; Pérez-Zenteno, Francisco; García-Hernansanz, Rodrigo; San Andres, Enrique; García-Hemme, Eric; Olea, Javier; Siegel, Jan; Gonzalo, Jose; Pastor, David; et al. (Semiconductor science and technology, 2025)
We present a detailed investigation on the properties of supersaturated GaAs using Cr implantation followed by nanosecond pulsed laser melting (PLM). A comparison between two different lasers was carried out (ArF and Nd:YAG). We have analyzed supersaturated samples by means of structural, electrical, optical, and optoelectronic techniques. Raman spectroscopy and Transmission electron microscopy results show a recovery of crystallinity after the PLM process. ToF-SIMS results reveal a Cr concentration above the solid solubility limit after the PLM process, featuring depth distribution depending on the type of laser used. The sheet resistance results obtained using van der Pauw configuration measurements show an activation of the implanted Cr in semi-insulating GaAs after PLM. Optical transmittance and Reflectance measurements show a sub-bandgap absorption (up to 10% for λ = 1250 nm) of the supersaturated GaAs:Cr related to the Cr incorporation, besides absorption induced by the PLM process itself. The origin of this sub-bandgap absorption has been analyzed by means of opto-electronic measurements revealing sub-bandgap photoresponsivity related to the absorption analyzed. The photoresponsivity measured below the bandgap originates from both the defects introduced by the PLM process and the states within the bandgap associated to the implanted Cr.